2010
DOI: 10.1002/msc.185
|View full text |Cite
|
Sign up to set email alerts
|

Self‐management strategies used during flares of rheumatoid arthritis in an ethnically diverse population

Abstract: This study identified a link between causal attribution of flares and the resultant self-management strategies. A perceived trigger of the flare in some patients formed a focus for their self-management strategies, whereas those who could not identify a cause aimed mainly to alleviate symptoms. A better understanding of patients' perspective in the context of disease flares will allow the development of educational programmes to facilitate more effective self-management of this important manifestation of disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(63 citation statements)
references
References 34 publications
2
60
0
1
Order By: Relevance
“…D'une part, l'aspect dynamique et subtil de l'ajustement des patients apparaît difficile à saisir lors une é valuation unique : seules des é tudes à mesures ré pé té es permettraient d'en rendre compte. D'autre part, l'usage d'une é chelle gé né ralisé e de coping [14,22] et d'une é chelle d'attributions causales ne permettent de saisir finement ni l'ajustement psychologique à cette maladie pré cise ni la mise en sens de la maladie par les patients. Le recours à des mé thodologies plus qualitatives apparaît donc né cessaire pour dé crire et comprendre, dans une perspective complé mentaire, les processus à l'oeuvre et la façon dont les patients é laborent leurs rapports à la maladie et à la fatigue [5,8,12,25].…”
Section: Resultsunclassified
“…D'une part, l'aspect dynamique et subtil de l'ajustement des patients apparaît difficile à saisir lors une é valuation unique : seules des é tudes à mesures ré pé té es permettraient d'en rendre compte. D'autre part, l'usage d'une é chelle gé né ralisé e de coping [14,22] et d'une é chelle d'attributions causales ne permettent de saisir finement ni l'ajustement psychologique à cette maladie pré cise ni la mise en sens de la maladie par les patients. Le recours à des mé thodologies plus qualitatives apparaît donc né cessaire pour dé crire et comprendre, dans une perspective complé mentaire, les processus à l'oeuvre et la façon dont les patients é laborent leurs rapports à la maladie et à la fatigue [5,8,12,25].…”
Section: Resultsunclassified
“…10 There is yet no consensus on what the best coping strategies are, and the positive association of HRQoL and strategies such as emotional expression (where patients readily express feelings or convey distress) appear conflicting. Although there is some evidence of cultural differences in coping strategies, 15,16 the population sample consisted of adolescents 15 or Asians in the setting of a Western society instead of in Asia. Although there is some evidence of cultural differences in coping strategies, 15,16 the population sample consisted of adolescents 15 or Asians in the setting of a Western society instead of in Asia.…”
Section: Introductionmentioning
confidence: 99%
“…One qualitative study [5] within an ethnically diverse group of RA patients found that patients who did not believe there was a cause to their flares were more likely to use strategies aimed at managing their symptoms such as using analgesics or distraction techniques. In contrast, those who believed they could identify the cause of their flare were more likely to use strategies aimed at eliminating these perceived causes such as altering their diet [5].…”
Section: Introductionmentioning
confidence: 99%
“…One qualitative study [5] within an ethnically diverse group of RA patients found that patients who did not believe there was a cause to their flares were more likely to use strategies aimed at managing their symptoms such as using analgesics or distraction techniques. In contrast, those who believed they could identify the cause of their flare were more likely to use strategies aimed at eliminating these perceived causes such as altering their diet [5]. A further qualitative study [6] with RA patients across five countries found that when in a flare, patients increase their usual level of self-management strategies by resting, pacing, applying heat or cold and escalating medications such as gluco-corticoids, often without seeking medical advice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation